Peran media sosial WhatsApp dalam kegiatan belajar mengajar di lingkungan pendidikan - Pandara, Riva Mey; Andika, Riksa Pribadi; Fadhlurrahman , Zhafran (EDUSHOPIA : Journal of Progressive Pedagogy, 2025)
This study examines the role of WhatsApp in supporting teaching and learning activities. It highlights its effectiveness in facilitating communication, distributing learning materials, and promoting group discussions. Despite technical challenges, WhatsApp enhances educational accessibility. In the context of Islamic education, it expands knowledge dissemination, strengthens teacher-student interaction, and fosters inclusivity and collaboration, aligning with Islamic educational value